A Hybrid Deep Learning Method for Early and Late Mild Cognitive Impairment Diagnosis With Incomplete Multimodal Data - Jin, Leiming; Zhao, Kun; Zhao, Yan; Che, Tongtong; Li, Shuyu (Frontiers in Neuroinformatics, 2022)
Multimodality neuroimages have been widely applied to diagnose mild cognitive impairment (MCI). However, the missing data problem is unavoidable. Most previously developed methods first train a generative adversarial network (GAN) to synthesize missing data and then train a classification network with the completed data. These methods independently train two networks with no information communication. Thus, the resulting GAN cannot focus on the crucial regions that are helpful for classification, and the classification network may not be suitable for these synthesized images. To overcome these issues, we propose a hybrid deep learning method. First, a classification network is pretrained with paired MRI and PET images. Afterwards, we use the pretrained classification network to guide a GAN by focusing on the features that are helpful for classification. Finally, we synthesize the missing PET images and use them with real MR images to fine-tune the classification model to make it better adapt to the synthesized images. We evaluate our proposed method on the ADNI dataset, and the results show that our method improves the accuracies obtained on the validation and testing sets by 3.84% and 5.82%, respectively. Moreover, our method increases the accuracies for the validation and testing sets by 7.7% and 9.09%, respectively, when we synthesize the missing PET images via our method. An ablation experiment shows that the last two stages are essential for our method. We also compare our method with other state-of-the-art methods, and our method achieves better classification performance.